Tony Morgan’s Performative Cinema in the Age of the “Cinematic Turn”: “Relational Films” (1969-1970), “Structural Films” (1969-1971) and Produkt Cinema (1971) - Bovier, François (Artium Quaestiones, 2020)
This article analyses the films, installations, performances and film projects of British artist, Tony Morgan, who is associated with Fluxus. Focusing on the years 1969–1971, we show the process of dematerialization and rematerialization inherent in his films – a distinctive feature of a cinematographic turning point in conceptual and postconceptual art. We discuss his film gallery, Produkt Cinema, an exceptional venue for producing and exhibiting films created exclusively for this specific location. We finally argue that, through the introduction of performative elements, his installations, generically entitled Structural Films, disrupt the minimalist ethos of ‘structural film’ (a term coined by P. Adams Sitney).